Optimizing Non-Aeronautical Revenue at Tjilik Riwut Palangka Raya Airport - Ardha Wulanigara; Juliater Simarmata (Dinasti International Journal of Digital Business Management, 2024)
Article on optimizing non-aeronautical revenue at Tjilik Riwut Palangka Raya Airport within the scope of marketing management science. This article aims to create hypotheses regarding the relationship between factors, which can then be used for further research in the field of human resource management. The research method used in this research is descriptive qualitative. The data used in this research comes from previous research which is still relevant to the current investigation. Data was collected from leading academic online platforms, including Publish or Perish, Google Scholar, digital reference books, and Sprott journals. The results of this literature research include: 1) The airport security system has an effect on increasing non-aeronautical revenue at Tjilik Riwut Palangka Raya Airport; 2) Terminal layout has an effect on increasing non-aeronautical revenue at Tjilik Riwut Palangka Raya Airport; and 3) Tenant promotions have an effect on increasing non-aeronautical revenue at Tjilik Riwut Palangka Raya Airport.